Konflik Tokoh Utama dan Perannya Terhadap Perkembangan Karakter Dalam Film Animasi Up - Alfarizi, Ramiz (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2023)
This study aims to analyze the conflict of the main character and its role in the development of the character in the film "UP" using a qualitative descriptive method. Through this approach, this study aims to describe and understand the conflict faced by the main character, Carl Fredicksen. In the selection stage of the film "UP" as the object of research, because it has a main character who experiences a complex and interesting conflict, data is collected through watching the film as a whole by focusing on the conflict faced by the main character. The data is analyzed descriptively to describe and identify the conflicts that occur. The results of the study show that Carl Fredicksen faces internal and external conflicts throughout the plot of the film. Qualitative descriptive analysis reveals how the conflict affects the development of the main character, internal conflict helps Carl to overcome his past and external conflict encourages Carl to show courage, and wisdom and to protect the people he cares about.